Effects of milking, over-milking and vacuum levels on front and rear quarter teats in dairy cows. Issue 4 (20th November 2021) - Vierbauch, Theresa; Peinhopf-Petz, Walter; Wittek, Thomas
Abstract: Mechanical forces to the teat and vacuum during milking negatively affect teat condition and may result in increased mastitis risk. We compared vacuum levels during milking and over-milking as well as teat condition before and after milking between front and rear teats. We expected that the lower milk yield of the front quarters would result in a longer over-milking and higher vacuum levels in front teats, resulting in morphological differences. The study comprised 540 dairy cows in 41 Austrian dairy farms with conventional milking systems. Before and after milking teats were visually assessed (colour, swelling, rings, hyperkeratosis) and teat dimensions (length, diameter, wall thickness, teat canal length) were measured manually and ultrasonographically. Vacuum measurements were taken using a vacuum measurement device attached to the cluster (short milk tube, pulsation tube and mouth-piece chamber). These various measurements of front and rear teats were compared and a multivariable analysis with backward stepwise procedure was used for inclusion or exclusion from the model. Front teats showed a poorer teat condition and were over-milked for longer in comparison to the rear teats. However, during milking and over-milking the vacuum levels in the mouthpiece chamber were significantly higher at the rear teats. The changes in front teat morphology were only partially caused by milking, over-milking and vacuum levels, with approximately 70% of the variation due to other, undetermined variables. Milking, over-milking and vacuum levels had no or very limited impact on the morphological changes of the rear teats.